Perspectives on resting-state functional magnetic resonance imaging research in vascular dementia - Jinhuan Yue; Jinhuan Yue; Peng Wang; Xiang-fa Guo; Zeyi Wei; Kaiting He; Nuo Li; Xiaoling Li; Qinhong Zhang; Qinhong Zhang; Xiaoqing Zhou (Frontiers in Aging Neuroscience)
Vascular dementia (VD) is a severe cognitive impairment syndrome resulting from various cerebrovascular diseases and is one of the leading causes of senile dementia. In recent years, its incidence has been steadily increasing. Given the lack of specific treatments for VD, early detection, diagnosis, and intervention are critically important. This review examines the existing literature on resting-state functional magnetic resonance imaging (rs-fMRI) in the context of VD, with a focus on key metrics such as amplitude of low-frequency fluctuations (ALFF), regional homogeneity (ReHo), and functional connectivity (FC). By analyzing changes in brain functional activity in VD patients as observed through rs-fMRI, this study aims to provide essential imaging insights that could support and enhance clinical treatment strategies.